(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2024)
Background: This study used eggshell powder(ESP) as reinforcement filler in (NR/NBR) blend to investigate the effect of this filler material on rheological properties. Materials and Methods: MSR 20 NR (50 pphr) was utilized, and (50 pphr) of NBR (1052, with 33 percent acrylonitrile contents) as a basic, carbon black N375(CB-20 pphr) was used. Eggshell powder (ESP) is a (97%) calcium carbonate (CaCO3) powder, two groups of samples were prepared with (0, 10, 30, and 50 phr) loading ratios of ESP and (CB-20 phr). Results: The results revealed that all properties decreased with increasing ESP and CB loading ratios except cure rate index(CR) properties increased with increasing loading ratios. Conclusion: From the results obtained Eggshell powder (ESP) was utilized in composites as biofillers. The eggshell powder (ESP) and CB-20 pphr used as reinforcement in the group (A) and (B) composites have been studied for their mechanical and rheological properties. As the loading ratios for (ESP) and (CB-20pphr) increased, the rheological parameters such as the smallest torque (ML), the ideal the Additionally assessed the maximum torque (MH),optimum cure time (Tc90), and scorch time (Ts2) all dropped, but the cure rate index (CR), which was rising.